Multimaterial Multinozzle Adaptive 3D Printing of Soft Materials. Issue 8 (13th March 2022) - Uzel, Sebastien G. M.; Weeks, Robert D.; Eriksson, Michael; Kokkinis, Dimitri; Lewis, Jennifer A.
Abstract: Direct ink writing is a facile method that enables biological, structural, and functional materials to be printed in three dimensions (3D). To date, this extrusion‐based method has primarily been used to soft materials in a layer‐wise manner on planar substrates. However, many emerging applications would benefit from the ability to conformally print materials of varying composition on substrates with arbitrary topography. Here, a high throughput platform based on multimaterial multinozzle adaptive 3D printing (MMA‐3DP) that provides independent control of nozzle height and seamless switching between inks is reported. To demonstrate the MMA‐3DP platform, conformally pattern viscoelastic inks composed of triblock copolymer, gelatin, and photopolymerizable polyacrylate materials onto complex substrates of varying topography, including those with surface defects that mimic skin abrasions or deep gouges. This platform opens new avenues for rapidly patterning soft materials for structural, functional, and biomedical applications. Abstract : Direct ink writing enables structural, functional, and biological materials to be printed in three dimensions. To advance this technique, this work creates a multinozzle multimaterial adaptive 3D printing method coupled with in‐line surface profilometry to rapidly printing soft materials onto substrates with arbitrary topography.